2002
DOI: 10.1103/physreve.66.021405
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on the equilibrium magnetization properties and structure of ferrofluids

Abstract: We investigate in detail the initial susceptibility, magnetization curves, and microstructure of ferrofluids in various concentration and particle dipole moment ranges by means of molecular dynamics simulations. We use the Ewald summation for the long-range dipolar interactions, take explicitly into account the translational and rotational degrees of freedom, coupled to a Langevin thermostat. When the dipolar interaction energy is comparable with the thermal energy, the simulation results on the magnetization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
195
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(219 citation statements)
references
References 35 publications
22
195
1
1
Order By: Relevance
“…This is similar to the adsorption of surfactant molecules on the surface of The results whereby the apparent magnetization or susceptibility of gels are larger than those of sols might appear to be contradictory because a computer simulation has shown that for a ferrosolid consisting of magnetic dipoles frozen at random locations but free to rotate, its susceptibility was considerably lower than for ferrofluids having fluidity (Wang, Holm, & Müller, 2002). This paradox can be explained in relation to hydrodynamic effects.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is similar to the adsorption of surfactant molecules on the surface of The results whereby the apparent magnetization or susceptibility of gels are larger than those of sols might appear to be contradictory because a computer simulation has shown that for a ferrosolid consisting of magnetic dipoles frozen at random locations but free to rotate, its susceptibility was considerably lower than for ferrofluids having fluidity (Wang, Holm, & Müller, 2002). This paradox can be explained in relation to hydrodynamic effects.…”
Section: Discussionmentioning
confidence: 75%
“…Experiments have shown that compared to a ferrofluids system without magnetic interaction (i.e. in the dilution), the reduced initial susceptibility of the system with magnetic interaction is less rather than larger as theory predicts (Wang et al, 2002;Taketomi et al, 2002). The difference may be understandable with the help of the "viscomagnetic effect" resulting from the hydrodynamic interaction.…”
Section: Resultsmentioning
confidence: 94%
“…For example, the one by Ivanov and Kuznetsova [124] compares well with experimental data. However, recent numerical simulations by Wang et al [126,128] for χ and M(H) are not well described by this theory when the volume fraction of the magnetic particles is small and the dipolar coupling is strong: they are better explained by a model of small non-interacting chains of different…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, s exhibits a maximum in density for both chains and rings. 39 The average ring and chain sizes in a system of non-interacting clusters are monotonically increasing functions of ρ, 40 and therefore we ascribe the presence of the maxima to either finite size effects or to intercluster interactions. 41,42 …”
Section: E Rings and Chains Size Distributions Without Branching Pointsmentioning
confidence: 99%